Hypomorphic mutations in ura6 confer 5-FOA resistance in fission yeast - Constance Kowal; Ying Liu; Claire Denis; Benoît Arcangioli; Stefania Francesconi; Serge Gangloff (PLoS ONE, 2026)
Genome integrity is essential for cellular survival and adaptation across diverse physiological states. The fission yeast Schizosaccharomyces pombe relies on conserved DNA repair pathways to maintain genome stability during proliferative growth and in the absence of cell division (quiescence/G0). Using 5-fluoroorotic acid (5-FOA) counter-selection, we examined spontaneous mutation accumulation in both conditions in a wild-type prototrophic strain. Unexpectedly, we identified in growing and quiescent cells a class of 5-FOA–resistant mutants that, unlike canonical ura4 or ura5 loss-of-function mutants, retain the ability to grow without uracil supplementation. Genetic analyses showed that this phenotype is stable and segregates as a single locus. Whole-genome sequencing of tetrads from independent crosses revealed multiple hypomorphic alleles of ura6 , which encodes the essential uridylate kinase. These alleles, comprising non-synonymous substitutions and an in-frame duplication, cluster within conserved regions of the protein and likely reduce production of the toxic 5-FOA–derived metabolite while preserving sufficient uracil biosynthesis.